Two-dimensional sonographic assessment of maximum placental length and thickness in the second trimester: a reproducibility study. (25th November 2014) - Milligan, Natasha; Rowden, Michael; Wright, Emily; Melamed, Nir; Lee, Yee Man; Windrim, Rory C; Kingdom, John C.
Abstract: Objectives : To determine the most reproducible method for the sonographic measurement of placental length. Methods : A prospective study of women with singleton pregnancies who underwent sonographic measurement of placental dimensions during mid-gestation. Two sonographers independently determined placental length using three different approaches (linear, curve-linear and panoramic) and placental thickness. Reproducibility was assessed by the Bland-Altman method and Interclass Correlation Coefficient (ICC). Results : Overall 34 women were included in the study. The curve-linear approach for the measurement of placental length was associated with the highest reproducibility (mean inter-observer difference of −0.10 cm) compared to the linear and panoramic approaches (mean difference −0.15 cm and −0.29 cm, respectively). Similarly, the ICC was highest for the curve-linear length approach (0.974) compared with the linear length and panoramic length approaches (0.956 and 0.926, respectively). Measurements of maximum placental thickness was also associated with a very good ICC (0.954). Conclusions : The curve-linear method for the measurement of placental length in the 2nd trimester appears to be the most reproducible approach. This technique may prove useful as an adjunct screening method, along with uterine artery Doppler and maximum placental thickness, to screen for major placental complications of pregnancy in the second trimester.